Relationship between Quality Signals’ Credibility, Trust in Food System Actors, Perceived Quality and Intention to Buy - Namanyi Pangsui, Tatiana; Gueye, Birahim; Christian Douanla, Jean (British Journal of Marketing Studies, 2020)
This paper investigates the relationship between brands/certification labels credibility, trust in food system actors, perceived quality and intention to buy food products. The sample, consists of a total of 317 rice consumers who purchase rice from modern retail outlets in cities of Saint-Louis, Thiès and Dakar. Data are collected through questionnaire and analyze through descriptive statistics, Pearson correlation coefficient, and an approach based on Ordinary Least Squares Regression and the Bootstrap Method. Brands and certification labels, considered here as two types of quality signals, are seperately studied. Findings indicate that brands/certification labels credibility has a direct and positive influence on intention to buy food products that have these types of quality signals. In addition, this relationship is mediated, both seperately and together, by trust in food system actors who issue these types of quality signals and perceived quality of these food products. A significant difference is found in the comparison to reveal the more powerful mediating variable in terms of mediation effect. The overall model for each type of quality signal is significant.